Принципи картографування в «Лінгвістичному атласі лексики на позначення рис людини в українських східностепових говірках Південної Донеччини» - Дворянкін, В. О.; Dvoriankin, V. O. (Чорноморський державний університет імені Петра Могили, 2016)
У статті розглянуто основні засади картографування в лінгвогеографічній праці, підготовленій на матеріалі номінацій рис людини в новожитніх українських східно-степових говірках Південної Донеччини. Висвітлено специфіку знаків, які використано в процесі створення різних типів лінгвістичних карт, а також у ході картографування різних структурних типів найменувань. Найголовніший ступінь протиставлень в атласі – лексичний, протиставлення другого ступеня – словотвірні. Укладений атлас об’єднує 95 лінгвістичних карт, серед яких лексичні, мотиваційні, семантичні, статистичні та зведена; уміщено легенди й коментарі до них. Діалектологічні карти свідчать про ареальне варіювання виявлених номінативних одиниць, ілюструють явища мінімальної диференціації та ареальної мозаїки. Вони є важливим джерелом для вивчення тенденцій просторової поведінки назв людини за зовнішніми ознаками та внутрішніми властивостями в українському східностеповому мовному ландшафті.

The issues concerning the study of newly formed Ukrainian eastern steppe dialects prove to be of current importance in modern linguistics, however the research area of this dialectal space in terms of linguo-geography is still not complete or accurate. In this context «Atlas of the Ukrainian Language» as well as a number of regional ones compiled by dialectologists as certain supplements for their dissertations (works of Z. Omel’chenko, L. Froliak, V. Drobotenko, N. Klymenko, N. Sidenko, N. Zahnitko, M. Kushmet) are considered to be one of the basic resources to investigate eastern steppe dialects and their area of distribution. The article aims at analyzing main factors of map-making in «Linguistic atlas of vocabulary for people’s features in Ukrainian eastern steppe dialects of South Donetsk region» that has been compiled as a supplement to the thesis «Nominative processes in Ukrainian eastern steppe dialects». While making thematic compilation of regional atlas linguo-geographical method has been used. The atlas comprises 95 linguistic maps, with 80 lexical ones, 6 motivational, 6 semantic, 2 statistic and 1 combined maps as well as comments on them. It includes only the maps that testify to the areal variety of the nominative units (69 maps). The lowest amount of linguistic maps represent the phenomenon of minimal diversity (20 maps) and areal mosaics (5 maps). The key contrasting established in the atlas is lexical (according to the roots). It is represented by means of geometric contours used in a certain sequence. The opposition of the second level is word-forming (according to word-forming formants of the same origin).Word-forming variants have been reproduced by modificators of a definite sign. A certain system of denotation comprised while compiling the atlas opens an opportunity to fully reflect the peculiarities of people’s features in Ukrainian eastern steppe linguistic landscape. The atlas compiled gives a possibility to follow geolinguistic tendencies typical to eastern steppe space based on the vocabulary related to people’s features. The perspectives for further research are recommended to be focused on comparative study of space behaviour of anthroponomens belonging to different temporal sections as well as revealing the dynamics of changes in dialectal continuum in question.
Principles of map-making in «Linguistic atlas of vocabulary for people’s features in ukrainian eastern steppe dialects of South Donetsk region»
Keywords: українські східностепові говірки; лексика на позначення рис людини; антропономен; лінгвістичний (діалектологічний) атлас; лінгвістична карта; ареальна поведінка номінативних одиниць; Ukrainian eastern steppe dialects; vocabulary for people’s features; anthroponomen; linguistic (dialectal) atlas; linguistic map; areal behaviour of nominative units